Historico-genetic Theory of Culture : On the Processual Logic of Cultural Change. - Dux, Günter (Sozialtheorie., 2014)
The book focuses on the modern understanding of human life-forms as constructs that followed an evolutionary history. The author thus finds science confronted with two questions: firstly, how the transgression of the virtual threshold between natural and cultural history was possible, secondly, how the socio-cultural constructs were able to develop in the course of history the way they did. The discussion concentrates on the problem of determining a processual logic in the development of societal structures as well as in the development of cognition. The focus of attention is the historico-gen.